Endonasal Endoscopic Approach to the Orbit (EEAO). (23rd August 2013) - Karkas, Alexandre; Theodosopoulos, Philip; Keller, Jeffrey T.; Zimmer, Lee A.
Abstract : Objectives: Describe the endoscopic anatomy of medial and inferior orbital walls and present 5 illustrative clinical cases. Methods: Two vessel‐injected cadavers (4 sides) were dissected through endoscopic endonasal transethmoid‐sphenoid‐maxillary approach. Results: Total ethmoidectomy and maxillary antrostomy were performed. Maxillary sinus roof was removed until reaching the infraorbital canal laterally. Anterior and posterior ethmoidal arteries were identified. Lamina papyracea was removed. Transnasal and transethmoidal sphenoidotomies were made. Periorbita was incised along medial and inferior orbital walls. Cavernous carotid artery was exposed and medialized to show oculomotor (CNIII), trochlear (CNIV), ophthalmic (CNV1), maxillary (CNV2), and abducent (CNVI) nerves in cavernous sinus. In superolateral wall of sphenoid sinus, the optocarotid recess was visualized as well as the optic nerve (CNII) and ophthalmic artery (OphA) entering the orbit. Anteriorly, the annulus tendineus of Zinn (ATZ) was found and incised, showing the insertion of superior, medial, and inferior rectus muscles with CNIII and its branches. CNII, nasociliary branch of CNV1, CNVI, and OphA also enter ATZ. Superior and inferior oblique muscles were seen outside ATZ. The anterior limit of dissection was the eye globe. Five clinical cases of EEAO (lymphoma, aspergilloma, hematoma, abscess, Graves' disease) will be presented. Conclusions: EEAO is ideal for inferior and medial lesions of the orbit. Contrary to craniotomies, EEAO exposes CNII without removing orbital roof and anterior clinoid. Contrary to orbitotomies, EEAO provides excellent visualization with angulated endoscopes. Limits are lesions of superior or lateral part of the orbit or lesions that need manipulation of CNII or a section of medial rectus muscle.